2021
DOI: 10.12659/ajcr.928957
|View full text |Cite
|
Sign up to set email alerts
|

May-Thurner Syndrome with Double Compression of the Iliac Vein: Lessons Based on a Case Report

Abstract: Patient: Female, 73-year-old Final Diagnosis: May-Thurner syndrome with double stenosis of the left common iliac vein Symptoms: Acute onset of worsening dyspnea, with lymphedema of the left lower limb Medication: — Clinical Procedure: — Specialty: Diagnostics, Laboratory • Radiology Objective: Rare disease Background: May-Thurner syndrome, also known as Cockett’s syndrome, is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Farina et al reported that dual compression of the LCIV was found due to osteophytes. 25 Similarly, in our study, compression of the distal LCIV was due to narrowing between lumbar degenerative change and the LCIA, and it accounted for half of bony MTS cases. Degenerative lumbar change is more likely to occur broadly rather than focally, and a larger range of the LCIV is more likely to be compressed in bony MTS.…”
Section: Discussionsupporting
confidence: 70%
“…Farina et al reported that dual compression of the LCIV was found due to osteophytes. 25 Similarly, in our study, compression of the distal LCIV was due to narrowing between lumbar degenerative change and the LCIA, and it accounted for half of bony MTS cases. Degenerative lumbar change is more likely to occur broadly rather than focally, and a larger range of the LCIV is more likely to be compressed in bony MTS.…”
Section: Discussionsupporting
confidence: 70%
“…Meng et al also prescribed rivaroxaban (10 mg/day) to MTS patients upon discharge [ 16 ]. However, Farina et al recommended a much higher dose rate (15 mg rivaroxaban twice a day in the first four weeks and 10 mg oral rivaroxaban with 100 mg aspirin per day for six months) compared to our study [ 17 ]. Several other case studies have also reported the use of rivaroxaban to prevent the recurrence of MTS [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 67%
“…1 Atypical cases of MTS including compression of the left external iliac vein, right iliac vein or the IVC, some of them depicted on DUS causing double vein compression have been reported in the literature. 11 Nevertheless, DUS has been shown to be a less reliable diagnostic test for iliac vein stenosis as it yields a smaller cross-sectional image of CIV and EIV compared to IVUS. 7 Furthermore, venography has been shown to be less accurate compared to IVUS regarding the location of the iliac stenosis and the ilio-caval confluence, as well as the distal landing zone when planning for stent placement.…”
Section: Discussionmentioning
confidence: 99%